Mental health issues during pregnancy - overview of the current knowledge - Majcher, Monika; Majcher, Magdalena; Świercz, Kamila; Górska, Dominika; Karwańska, Aleksandra; Kulbat, Mateusz; Brzychczy, Piotr; Sierpień, Małgorzata; Pikulicka, Agata; Kulbat, Aleksandra (Journal of Education, Health and Sport, 2023)
Depressive disorders of antenatal and postnatal period are diagnostic challenge, as well as increasingly frequent social problem. Incidence of antenatal depression varies from 10% to 16%. Around one third of all postpartum depression cases has its beginning during the antenatal period. From the beginning of 2019, Ministry of Health’s regulations specified for the first time the recommendation to perform screening of depressive symptoms - twice during the pregnancy and once during the perinatal period, defined as the first six weeks after the delivery. Therefore the review of current studies in the subject of mental health issues during pregnancy was conducted in order to establish possible risk factors.